Heat prevention and insulation composite material with light double-gradient structure and preparation method of heat prevention and insulation composite material
By forming a lightweight dual-gradient structure with heat-resistant and heat-insulating gradient layers on the fiber reinforcement, the problem of insufficient density and heat insulation performance of existing thermal protection materials is solved, and effective protection is achieved in ultra-high temperature environments.
Patent Information
- Application Number
- CN202510963287.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-14
- Publication Date
- 2025-11-04
AI Technical Summary
Existing ultra-high temperature thermal protection materials are gradually failing to meet the requirements of aerospace equipment in terms of density, thermal insulation performance and thermal protection efficiency. Furthermore, carbon/carbon, carbon/resin, and carbon/ceramic materials are prone to oxidation and structural damage in the presence of oxygen.
The lightweight, dual-gradient heat-insulating composite material uses fiber felt or short fiber bonded composite material as reinforcement, combined with MAX phase ceramics and infrared shielding agents, to form a heat-insulating and heat-resistant gradient layer through gradient impregnation, and uses phenolic hybrid oxide aerogel as the matrix to provide structural support and protection.
It achieves lightweight, excellent heat protection and insulation properties, with a density of less than 1.0 g/cm3, can withstand ultra-high temperatures above 1800℃, has a thermal conductivity of less than 0.1 W/m·K, and does not suffer structural damage at high temperatures. The manufacturing process is simple and low in cost.
Smart Images

Figure CN120887674A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of ultra-high temperature heat protection materials, and particularly relates to a light-weight double-gradient structure heat protection composite material and a preparation method thereof. BACKGROUND
[0002] When a hypersonic vehicle such as a spacecraft, a return capsule and a strategic and tactical missile passes through the atmosphere or returns from outer space, the surface will be subjected to strong friction with the atmosphere, resulting in extremely high temperature and strong airflow shear effect, and the temperature at positions such as the nose cone and the windward surface reaches 1800℃ or above, like the phenomenon of a meteorite passing through the atmosphere and burning violently, which will pose a great threat to the vehicle and the personnel inside, therefore, high-efficiency heat protection materials must be used to protect the vehicle. Carbon / carbon (C / C), carbon / resin and carbon / ceramic supported by carbon fibers are three most important heat protection materials. In particular, C / C composite materials are suitable for the most extreme positions such as the nose cone and the windward surface due to their light weight, high melting point and high thermal stability. However, carbon / carbon (C / C), carbon / resin and carbon / ceramic will be rapidly oxidized and structurally damaged in an oxygen-containing environment. Moreover, with the development of space technology, the existing heat protection materials gradually cannot meet the requirements in terms of density, heat insulation performance and heat protection efficiency. SUMMARY
[0003] To solve the problems existing in the existing ultra-high temperature heat protection materials and their preparation technology, the present application provides a light-weight double-gradient structure heat protection composite material and a preparation method thereof.
[0004] The preparation method of the light-weight double-gradient structure heat protection composite material of the present application uses a fiber felt or a short fiber adhesive composite material as a reinforcing body, utilizes MAX phase ceramics and an infrared shielding agent with excellent heat protection performance, forms a double-gradient heat protection structure through gradient impregnation, and uses ultra-light phenolic hybrid oxide aerogel as a matrix to improve the heat insulation performance of the composite material and provide protection and structural support for the fibers and the overall structure. The method specifically includes the following steps:
[0005] Step 1: Fiber surface treatment:
[0006] A coupling agent ethanol solution with a specified concentration is prepared, and the selected fiber reinforcing body is vacuum-impregnated in the coupling agent solution for a specified time, and then dried for standby use.
[0007] Step 2: Preparation of infrared shielding gradient layer:
[0008] Selecting ceramic powder with infrared shielding effect at high temperature, blending infrared shielding agent, phenolic resin, ethanol and dispersant, controlling the average particle size and solid content of the infrared shielding agent, dissolving the phenolic resin to obtain stable slurry without sedimentation; the fiber reinforced body treated in step 1 is immersed in the infrared shielding agent slurry, kept for a specified time, taken out and dried in an oven, and the ceramic powder is mainly impregnated into the interior; repeat the above impregnation process several times to obtain an infrared shielding gradient layer; finally, the phenolic resin is cured in the oven according to the specified program.
[0009] Step 3: Preparation of MAX phase heat protection gradient layer:
[0010] Selecting MAX phase ceramic powder with excellent ablation resistance; blending MAX phase ceramic powder, phenolic resin, ethanol and dispersant, controlling the average particle size and solid content of the MAX phase ceramic powder, dissolving the phenolic resin to obtain stable slurry without sedimentation; the fiber reinforced body treated in step 2 is immersed in the MAX phase ceramic powder slurry, kept for a specified time, taken out and dried in an oven, and the ceramic powder mainly forms a dense heat protection layer on the surface; repeat the above impregnation process several times to obtain a dense heat protection layer; finally, the phenolic resin is cured in the oven according to the specified program.
[0011] Step 4: Preparation of phenolic hybrid oxide aerogel sol:
[0012] First, hydrolyze the oxide aerogel precursor at a specified temperature to form a sol; then add phenolic resin, curing agent and coagulant to the sol.
[0013] Step 5: Vacuum impregnation, aging and drying:
[0014] Immerse the heat insulation surface of the composite material in step 3 into the phenolic hybrid oxide aerogel sol in step 4, the sol will enter the pores of the heat insulation surface of the composite material and gel in a specified time; take out the composite material, put it into a reaction kettle, seal and age and cure at a specified temperature; finally, directly dry at room temperature or heat dry in an oven to obtain a lightweight double gradient structure heat protection and insulation composite material.
[0015] Further, in step 1, the structure of the fiber reinforced body includes 2.5D fiber needle felt, three-dimensional fiber woven body and short fiber bonded composite material; the type of fiber reinforced body includes carbon fiber, quartz fiber, high silicon oxygen fiber, mullite fiber or hybrid woven body of the above fibers.
[0016] The coupling agent includes γ-aminopropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-glycidyl ether propyl trimethoxysilane and γ-methacryloyl propyl trimethoxysilane; the mass percentage of the coupling agent solution is 20-50%.
[0017] Further, in step 2, the infrared shielding agent includes SiC, rutile TiO2, Ti3SiC2, ZrSiO4, K2O·6TiO2; the solid content of the infrared shielding agent ranges from 20 to 30%, and the average particle size ranges from 200 to 500 nanometers; the dipping time is 2 to 10 minutes, and the dipping frequency is 1 to 6 times.
[0018] Further, in step 3, the MAX phase heat-resistant ceramic powder includes one or more of Ti2AlC, Ti3AlC2, Cr2AlC, MoAlB, and Nb4AlC3; the solid content of the MAX phase heat-resistant ceramic powder is 30 to 60%, and the average particle size ranges from 200 to 500 nanometers; the dipping time is 2 to 5 minutes, and the dipping frequency is 2 to 5 times.
[0019] Further, the phenolic resin is a boron-modified phenolic resin, and the curing procedure of the phenolic resin is 150 to 180 DEG C for 1 to 3 hours and 180 to 200 DEG C for 1 to 2 hours; the dispersing agent includes polyethylene imine and polyacrylamide.
[0020] Further, in step 4, the oxide aerogel includes one or more of SiO2, Al2O3, ZrO2, Y2O3, TiO2, and La2O3; the content of the phenolic resin is 10 to 40% of the total mass of the sol.
[0021] Further, in step 5, the pressure of vacuum dipping is -0.5 to 0.1 MPa, and the dipping time is 10 to 60 minutes; the drying mode is normal temperature and pressure drying or oven normal pressure drying, the drying temperature is 30 to 120 DEG C, and the drying time is 12 to 48 hours.
[0022] A light double-gradient structure heat-resistant composite material is prepared by the above-mentioned preparation method of the light double-gradient structure heat-resistant composite material.
[0023] The present application has the following beneficial technical effects:
[0024] 1. The present application utilizes MAX phase ceramics and infrared shielding agents, forms a double-gradient structure through gradient dipping, and uses ultra-light phenolic hybrid oxide aerogel as a matrix to improve the heat insulation performance of the composite material and provide protection and structural support for fibers and the overall structure.
[0025] 2. The composite material prepared by the present application has the advantages of light weight, excellent heat resistance and heat insulation performance: the density is less than 1.0 g / cm 3 ; can resist ultra-high temperatures above 1800 DEG C without obvious structural damage; the thermal conductivity of the composite material forms a gradient from the heat-resistant surface to the heat-insulating surface, and the thermal conductivity of the heat-insulating surface is less than 0.1 W / m·K.
[0026] 3. The preparation process is simple, low in cost, short in preparation period, does not need large and expensive equipment, and is easy to realize large-scale production. BRIEF DESCRIPTION OF DRAWINGS
[0027] Figure 1 A preparation flow chart of the light double-gradient structure heat-proof and heat-insulating composite material.
[0028] Figure 2 A structure schematic diagram of the light double-gradient structure heat-proof and heat-insulating composite material.
[0029] Figure 3 A sample macroscopic photo in the preparation process of Example 1.
[0030] Figure 4 A scanning electron microscope photo after plasma flame impact of Example 1. DETAILED DESCRIPTION
[0031] The application will be further described in detail below in combination with the drawings and specific examples.
[0032] The application designs a double-gradient structure composed of an oxide aerogel matrix, an infrared light-shielding layer and a heat-proof layer in the fiber reinforcement body to solve the problems of complex preparation process, easy oxidation, separation and deficiency of heat-proof and heat-insulating performance of the existing heat-proof materials. The oxide aerogel has excellent performances such as extremely low density and thermal conductivity, high thermal stability and chemical stability, high specific surface area and porosity, which will ensure that the heat-proof material has extremely low density, extremely high heat-insulating performance and provides protection for the carbon fiber to prevent its oxidation; the infrared light-shielding gradient layer will reflect infrared radiation at high temperature to improve the heat-insulating performance of the heat-proof material; the heat-proof gradient layer is mainly composed of ternary layered ceramics (MAX phase), which will improve the heat-proof performance of the heat-proof material by using the excellent ablation resistance of the MAX phase; the double-gradient structure design will form a composition gradient structure by using the attraction of capillary tension and the anti-gravity diffusion of the slurry in the fiber, which will ensure excellent heat-proof and heat-insulating performance of the material while not losing the lightweight feature.
[0033] The preparation method of the lightweight double-gradient structure heat-resistant and heat-insulating composite material of the present application uses a fiber felt or short fiber adhesive composite as a reinforcing body, divides its opposite two faces into a heat-resistant face and a heat-insulating face, directly faces the aerodynamic heating on the heat-resistant face to play a heat protection role, and keeps the heat-insulating face away from the aerodynamic heating to play a role of heat insulation and protection of the fiber skeleton inside. On the heat-resistant face, an infrared shielding and heat-resistant double-gradient heat-resistant structure is designed. By immersing the heat-resistant face in a slurry, the infrared shielding and heat-resistant slurry will diffuse into the fiber reinforcing body pores against gravity under the action of capillary tension and form a composition gradient in the vertical direction. By controlling the solid content of the infrared shielding and heat-resistant slurry and the immersion mode, the internal gradient and surface gradient are realized. The infrared shielding slurry forms an internal gradient layer to shield infrared radiation at ultra-high temperature, improve the heat-insulating effect, and improve the combination of the heat-insulating layer and the heat-resistant layer. The heat-resistant slurry mainly forms a dense gradient layer on the surface to realize efficient heat protection. The heat-insulating face uses phenolic oxide aerogel, uses the ultra-low density and thermal conductivity and high-temperature stability of the aerogel to ensure the heat-insulating performance of the designed heat protection material and provide structural support and protection for the fiber and the whole.
[0034] The preparation method flow of the lightweight double-gradient structure heat-resistant and heat-insulating composite material of the present application is shown in Figure 1 The specific steps include the following steps:
[0035] Step 1: Fiber surface treatment:
[0036] A coupling agent ethanol solution with a specified concentration is prepared, and the selected fiber reinforcing body is vacuum immersed in the coupling agent solution for a specified time, and dried for standby use.
[0037] The structure of the fiber reinforcing body includes a 2.5D fiber needle felt, a three-dimensional fiber woven body, and a short fiber adhesive composite; the type of the fiber reinforcing body includes carbon fiber, quartz fiber, high-silica fiber, mullite fiber, or a hybrid woven body of the above fibers.
[0038] The coupling agent includes γ-aminopropyl triethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-glycidyl ether propyl trimethoxysilane, and γ-methacryloyl propyl trimethoxysilane; the mass percentage of the coupling agent solution is 20-50%.
[0039] Step 2: Infrared shielding gradient layer preparation:
[0040] Selecting ceramic powder with infrared shielding effect at high temperature, blending infrared shielding agent, phenolic resin, ethanol and dispersant, controlling the average particle size and solid content of the infrared shielding agent, dissolving the phenolic resin to obtain stable slurry without sedimentation; the fiber reinforcement treated in step 1 is immersed in the infrared shielding agent slurry for a specified time, and then taken out and dried in an oven, and the ceramic powder is mainly impregnated into the interior; the above impregnation process is repeated several times to obtain an infrared shielding gradient layer; finally, the phenolic resin is cured in the oven according to the specified program.
[0041] The infrared shielding agent includes SiC, rutile TiO2, Ti3SiC2, ZrSiO4, K2O·6TiO2; the solid content of the infrared shielding agent ranges from 20 to 30%, and the average particle size ranges from 200 to 500 nanometers; the impregnation time is 2-10 minutes, and the impregnation times is 1-6 times.
[0042] Step 3: Preparation of MAX phase heat protection gradient layer:
[0043] Selecting MAX phase ceramic powder with excellent ablation resistance; blending MAX phase ceramic powder, phenolic resin, ethanol and dispersant, controlling the average particle size and solid content of the MAX phase ceramic powder, dissolving the phenolic resin to obtain stable slurry without sedimentation; the fiber reinforcement treated in step 2 is immersed in the MAX phase ceramic powder slurry for a specified time, and then taken out and dried in an oven, and the ceramic powder mainly forms a dense heat protection layer on the surface; the above impregnation process is repeated several times to obtain a dense heat protection layer; finally, the phenolic resin is cured in the oven according to the specified program.
[0044] The MAX phase heat protection ceramic powder includes one or more of Ti2AlC, Ti3AlC2, Cr2AlC, MoAlB, Nb4AlC3; the solid content of the MAX phase heat protection ceramic powder is 30-60%, and the average particle size ranges from 200 to 500 nanometers; the impregnation time is 2-5 minutes, and the impregnation times is 2-5 times.
[0045] Step 4: Preparation of phenolic hybrid oxide aerogel sol:
[0046] First, the oxide aerogel precursor is hydrolyzed to form a sol at a specified temperature; then, phenolic resin, curing agent and coagulant are added to the sol.
[0047] The oxide aerogel includes one or more of SiO2, Al2O3, ZrO2, Y2O3, TiO2, La2O3; the content of the phenolic resin is 10-40% of the total mass of the sol.
[0048] Step 5: Vacuum impregnation, aging and drying:
[0049] The heat insulation surface of the composite material of step 3 is immersed into the phenolic hybrid oxide aerogel sol of step 4, the sol will enter the heat insulation surface pores of the composite material and gel in a specified time; the composite material is taken out and placed in a reaction kettle, sealed and aged and cured at a specified temperature; finally, direct normal temperature drying or oven heating drying is performed, and a lightweight double gradient structure heat protection and insulation composite material is obtained.
[0050] The pressure of vacuum impregnation is-0.5-0.1 MPa, the impregnation time is 10-60 minutes; the drying mode is normal temperature and pressure drying or oven normal pressure drying, the drying temperature is 30-120 DEG C, and the drying time is 12-48 hours.
[0051] The lightweight double gradient structure heat protection and insulation composite material structure of the application is shown in the drawing. Figure 2 The lightweight double gradient structure heat protection and insulation composite material is prepared by the preparation method of the lightweight double gradient structure heat protection and insulation composite material.
[0052] Example 1
[0053] S1, fiber surface treatment: a 20% mass fraction of γ-aminopropyl triethoxysilane ethanol solution is prepared, and the polyacrylonitrile-based carbon fiber needle felt is vacuum impregnated in the coupling agent solution for 1 hour and dried for standby.
[0054] S2, infrared shielding gradient layer preparation: SiC, boron modified phenolic resin, ethanol and polyethylene imine are blended, the average particle size and solid content of SiC are 500 nanometers and 25% respectively; the fiber reinforced body treated in S1 is impregnated into the SiC slurry for 3 millimeters for 3 minutes, and then taken out and dried in an oven, and the ceramic powder is mainly impregnated into the inside; the above impregnation process is repeated for 3 times to obtain an infrared shielding gradient layer; finally, the phenolic resin is cured in an oven at 150 DEG C for 3 hours and at 180 DEG C for 2 hours.
[0055] S3, MAX phase heat protection gradient layer preparation: Cr2AlC ceramic powder is selected, and Cr2AlC ceramic powder, boron modified phenolic resin, ethanol and ethylene imine are blended, the average particle size and solid content of Cr2AlC ceramic powder are 500 nanometers and 35% respectively; the fiber reinforced body treated in S2 is impregnated into the Cr2AlC ceramic powder slurry for 2 millimeters for 2 minutes, and then taken out and dried in an oven, and the ceramic powder mainly forms a dense heat protection layer on the surface; the above impregnation process is repeated for 3 times to obtain a dense heat protection layer; finally, the phenolic resin is cured in an oven at 150 DEG C for 3 hours and at 180 DEG C for 2 hours.
[0056] S4, preparation of phenolic hybrid oxide aerogel sol: firstly, alumina aerogel precursor is hydrolyzed to form a sol at 60 DEG C; then, boron modified phenolic resin, curing hexamethylene tetramine agent and coagulation accelerator propylene oxide are added into the sol.
[0057] S5. Vacuum Impregnation, Aging and Drying: The insulating surface of the composite material from S3 is completely immersed in the impregnation solution. The hybrid sol will enter the pores of the insulating surface of the composite material and gel within 30 minutes. The composite material is then removed and placed in a reaction vessel for sealed aging at 60°C and curing at 180°C for 2 hours. Finally, it is dried in an oven at 100°C for 16 hours to obtain a lightweight, dual-gradient structure heat-insulating composite material.
[0058] The density of this lightweight, dual-gradient thermal insulation composite material is 0.89 g / cm³. 3 The internal thermal insulation aerogel has a thermal conductivity of 0.05 W / m·K. It maintains structural integrity under nitrogen plasma flame impact at 1800℃ with an ablation rate close to 0. Under plasma flame impact at 2000℃ for 60 seconds, the linear ablation rate and mass ablation rate are as low as 4.2 μm / s and 2.75 mg / s, respectively.
[0059] Example 2
[0060] S1. Fiber surface treatment: Prepare a 25% mass fraction γ-aminopropyltriethoxysilane ethanol solution, vacuum impregnate the polyacrylonitrile-based carbon fiber needle-punched felt in the coupling agent solution for 1 hour, and then dry it for later use.
[0061] S2. Preparation of Infrared Shielding Gradient Layer: ZrSiO4, boron-modified phenolic resin, ethanol, and polyethyleneimine were blended. The average particle size and solid content of ZrSiO4 were 400 nm and 20%, respectively. The fiber reinforcement treated in S1 was impregnated into the ZrSiO4 slurry for 2 mm and held for 2 minutes. After removal, it was dried in an oven, and the ceramic powder was mainly impregnated into the interior. The above impregnation process was repeated 3 times to obtain the infrared shielding gradient layer. Finally, the phenolic resin was cured in an oven at 150°C for 3 hours and 180°C for 2 hours.
[0062] Preparation of S3 and MAX phase thermal gradient layers: MoAlB ceramic powder was selected and blended with boron-modified phenolic resin, ethanol, and ethyleneimine. The average particle size and solid content of the MoAlB ceramic powder were 400 nm and 40%, respectively. The fiber reinforcement treated with S2 was impregnated into the MoAlB ceramic powder slurry by 1 mm and held for 4 minutes. After removal, it was dried in an oven. The ceramic powder mainly formed a dense thermal barrier layer on the surface. The above impregnation process was repeated 3 times to obtain a dense thermal barrier layer. Finally, the phenolic resin was cured in an oven at 150℃ for 3 hours and 180℃ for 2 hours.
[0063] S4. Preparation of phenolic hybrid oxide aerogel sol: First, the alumina-silica aerogel precursor is hydrolyzed at 70°C to form a sol; then, boron-modified phenolic resin, hexamethylenetetramine curing agent, and propylene oxide coagulant are added to the sol.
[0064] S5, vacuum impregnation, aging and drying: the thermal insulation surface of the composite material of S3 is immersed in the whole, and the hybrid sol will enter the thermal insulation surface pores of the composite material and gel in 50 minutes; the composite material is taken out and put into a reaction kettle for sealed aging at 70°C and curing at 180°C for 2 hours. Finally, drying at 80°C for 24 hours in an oven, a lightweight double-gradient structure heat-shielding composite material is obtained.
[0065] The macroscopic photos of the sample during the preparation process of Example 1 are shown in Figure 3 The scanning electron microscope photos after plasma flame impact are shown in Figure 4 The density of the lightweight double-gradient structure heat-shielding composite material is 0.93 g / cm 3 , the thermal conductivity of the internal thermal insulation aerogel is 0.040 W / m·K, the structure remains intact under the impact of a nitrogen plasma flame at 1800°C, the ablation rate is close to 0, and the linear ablation rate and mass ablation rate are as low as 2.31 μm / s and 1.92 mg / s respectively under the impact of a plasma flame at 2000°C for 60 seconds.
[0066] Example 3
[0067] S1, fiber surface treatment: a 25% mass fraction of γ-glycidoxypropyltrimethoxysilane ethanol solution is prepared, and the carbon-bonded carbon fiber-quartz fiber composite material is vacuum-impregnated in the coupling agent solution for 1 hour and dried for standby use.
[0068] S2, preparation of infrared shielding gradient layer: Ti3SiC2, boron-modified phenolic resin, ethanol and polyethyleneimine are blended, the average particle size and solid content of Ti3SiC2 are 500 nanometers and 20% respectively; the fiber reinforcement treated in S1 is immersed in the Ti3SiC2 slurry for 3 millimeters for 5 minutes, and then taken out and dried in an oven, and the ceramic powder is mainly impregnated into the inside; the above impregnation process is repeated twice to obtain an infrared shielding gradient layer; finally, the phenolic resin is cured in an oven at 150°C for 3 hours and at 180°C for 2 hours.
[0069] S3, preparation of MAX phase heat shielding gradient layer: Ti3AlC2 ceramic powder is selected, and Ti3AlC2 ceramic powder, boron-modified phenolic resin, ethanol and ethyleneimine are blended, the average particle size and solid content of MoAlB ceramic powder are 500 nanometers and 50% respectively; the fiber reinforcement treated in S2 is immersed in the Ti3AlC2 ceramic powder slurry for 1 millimeter for 4 minutes, and then taken out and dried in an oven, and the ceramic powder mainly forms a dense heat shielding layer on the surface; the above impregnation process is repeated 4 times to obtain a dense heat shielding layer; finally, the phenolic resin is cured in an oven at 150°C for 3 hours and at 180°C for 2 hours.
[0070] S4, Preparation of phenolic hybrid oxide aerogel sol: firstly, hydrolyze the alumina-yttria-silica aerogel precursor at 70℃ to form a sol; then add boron-modified phenolic resin, curing hexamethylenetetramine agent and coagulant propylene oxide into the sol.
[0071] S5, Vacuum impregnation, aging and drying: immerse the thermal insulation surface of the composite material of S3 into the hybrid sol, which will enter the pores of the thermal insulation surface of the composite material and gel within 60 minutes; take out the composite material and put it into a reaction kettle for sealed aging at 70℃ and curing at 180℃ for 2 hours. Finally, dry in an oven at 120℃ for 16 hours to obtain a lightweight double-gradient structure heat-resistant and heat-insulating composite material.
[0072] The density of the lightweight double-gradient structure heat-resistant and heat-insulating composite material is 0.95 g / cm 3 The thermal conductivity of the internal thermal insulation aerogel is 0.063 W / m·K, the structure remains intact under the impact of a nitrogen plasma flame at 1800℃, the ablation rate is close to 0, and the linear ablation rate and mass ablation rate are as low as 1.45 μm / s and 2.34 mg / s, respectively, under the impact of a plasma flame at 2000℃ for 60 seconds.
[0073] In summary, the composite material prepared by the present application has the advantages of lightweight, excellent heat-resistant and heat-insulating performance, density <1.0 g / cm 3 It can resist ultra-high temperatures above 1800℃ without obvious structural damage; the thermal conductivity of the composite material forms a gradient from the heat-resistant surface to the heat-insulating surface, and the thermal conductivity of the heat-insulating surface is less than 0.1 W / m·K. The lightweight double-gradient structure heat-resistant and heat-insulating composite material of the present application solves the problems of separation of heat-resistant and heat-insulating performance, complex preparation process, easy oxidation of carbon fibers and insufficient heat-resistant and heat-insulating performance of heat protection materials, and is expected to be applied in ultra-high temperature environments above 1800℃.
Claims
1. A method for preparing a lightweight, dual-gradient structure heat-insulating composite material, characterized in that, Using fiber felt or short fiber bonded composite materials as reinforcement, and utilizing MAX phase ceramics with excellent heat-insulating properties and infrared shielding agents, a double-gradient heat-insulating structure is formed through gradient impregnation. An ultra-lightweight phenolic hybrid oxide aerogel serves as the matrix, enhancing the thermal insulation performance of the composite material and providing protection and structural support for the fibers and the overall structure. Specifically, the process includes the following steps: Step 1: Fiber surface treatment: Prepare a coupling agent ethanol solution of a specified concentration, vacuum impregnate the selected fiber reinforcement in the coupling agent solution for a specified time, and dry it for later use. Step 2: Fabrication of the infrared masking gradient layer: Ceramic powder with infrared shielding properties at high temperatures is selected. An infrared shielding agent, phenolic resin, ethanol, and dispersant are blended together. The average particle size and solid content of the infrared shielding agent are controlled, and the phenolic resin is dissolved to obtain a stable, non-settling slurry. The fiber reinforcement treated in step 1 is impregnated into the infrared shielding agent slurry and kept for a specified time. After removal, it is dried in an oven, allowing the ceramic powder to penetrate the interior. This impregnation process is repeated several times to obtain an infrared shielding gradient layer. Finally, the phenolic resin is cured in an oven according to a specified procedure. Step 3: Preparation of the MAX phase thermal gradient barrier layer: MAX phase ceramic powder with excellent ablation resistance was selected; MAX phase ceramic powder, phenolic resin, ethanol, and dispersant were blended, and the average particle size and solid content of the MAX phase ceramic powder were controlled to dissolve the phenolic resin and obtain a stable, non-settling slurry; the fiber reinforcement treated in step 2 was impregnated into the MAX phase ceramic powder slurry and kept for a specified time, then removed and dried in an oven, where the ceramic powder mainly formed a dense heat-insulating layer on the surface; the above impregnation process was repeated several times to obtain a dense heat-insulating layer; finally, the phenolic resin was cured in an oven according to a specified procedure. Step 4: Preparation of phenolic hybrid oxide aerogel sol: First, the oxide aerogel precursor is hydrolyzed at a specified temperature to form a sol; then, phenolic resin, curing agent and coagulation accelerator are added to the sol. Step 5: Vacuum impregnation, aging and drying: The heat-insulating surface of the composite material from step 3 is immersed in the phenolic hybrid oxide aerogel sol from step 4. The sol will enter the heat-insulating pores of the composite material and gel within a specified time. The composite material is then removed, placed in a reaction vessel, and sealed for aging and curing at a specified temperature. Finally, it is dried directly at room temperature or heated in an oven to obtain a lightweight, dual-gradient structure heat-insulating composite material.
2. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, In step 1, the structure of the fiber reinforcement includes 2.5D fiber needle-punched felt, three-dimensional fiber braid, and short fiber bonded composite material; the type of fiber reinforcement includes carbon fiber, quartz fiber, high silica fiber, mullite fiber, or a hybrid braid of the above fibers. The coupling agents include γ-aminopropyltriethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-methacryloyloxypropyltrimethoxysilane; the mass percentage of the coupling agent solution is 20-50%.
3. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, In step 2, the infrared masking agent includes SiC, rutile TiO2, Ti3SiC2, ZrSiO4, and K2O·6TiO2; the solid content of the infrared masking agent ranges from 20% to 30%, and the average particle size ranges from 200 to 500 nanometers; the impregnation time is 2 to 10 minutes, and the number of impregnations is 1 to 6.
4. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, In step 3, the MAX phase heat-resistant ceramic powder includes one or more composites of Ti2AlC, Ti3AlC2, Cr2AlC, MoAlB, and Nb4AlC3; the solid content of the MAX phase heat-resistant ceramic powder is 30-60%, the average particle size ranges from 200 to 500 nanometers; the impregnation time is 2-5 minutes, and the number of impregnations is 2-5 times.
5. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, The phenolic resin is a boron-modified phenolic resin, and the curing process of the phenolic resin is 150-180℃ for 1-3 hours and 180-200℃ for 1-2 hours; the dispersant includes polyethyleneimine and polyacrylamide.
6. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, In step 4, the oxide aerogel includes one or more composites of SiO2, Al2O3, ZrO2, Y2O3, TiO2, and La2O3; the content of phenolic resin is 10-40% of the total mass of the sol.
7. The method for preparing a lightweight, dual-gradient structure heat-insulating composite material according to claim 1, characterized in that, In step 5, the vacuum impregnation pressure is -0.5-0.1 MPa, the impregnation time is 10-60 minutes, and the drying method is room temperature and pressure drying or oven drying at normal pressure, the drying temperature is 30-120℃, and the drying time is 12-48 hours.
8. A lightweight, dual-gradient structure heat-insulating composite material, characterized in that, The lightweight, dual-gradient structure heat-insulating composite material is prepared by any one of the preparation methods described in claims 1-7.